2020
DOI: 10.1002/jsfa.10975
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative identification of the edible oil storage period using a homemade portable electronic nose combined with multivariate analysis

Abstract: BACKGROUND: The edible oil storage period is one of the important indicators for evaluating the intrinsic quality of edible oil. The present study aimed to develop a portable electronic nose device for the qualitative identification of the edible oil storage period. First, four metal oxide semiconductor gas sensors, comprising TGS2600, TGS2611, TGS2620 and MQ138, were selected to prepare a sensor array to assemble a portable electronic nose device. Second, the homemade portable electronic nose device was used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…The electronic nose (E-nose) is a low-cost device made from a combination of sensors that allows samples with different aroma profiles to be discriminated in different types of matrices. In the wine matrix, its use has been studied to avoid the development of unpleasant flavours and aromas in final wines [17]; in edible oils, it has been used for the qualitative evaluation of the storage period [18]; in citrus fruits, for the detection of infections [19]; in garlic, for the early detection and classification of fungal infections [20]. This device has also been used to classify the quality of olives from different olive trees [21] or even to differentiate table olives with abnormal fermentations [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…The electronic nose (E-nose) is a low-cost device made from a combination of sensors that allows samples with different aroma profiles to be discriminated in different types of matrices. In the wine matrix, its use has been studied to avoid the development of unpleasant flavours and aromas in final wines [17]; in edible oils, it has been used for the qualitative evaluation of the storage period [18]; in citrus fruits, for the detection of infections [19]; in garlic, for the early detection and classification of fungal infections [20]. This device has also been used to classify the quality of olives from different olive trees [21] or even to differentiate table olives with abnormal fermentations [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…20 The core idea of the SVR model is to use the kernel function to transform and map a nonlinear problem into a high-dimensional space. 21 In the high-dimensional space, the problem becomes a linear problem by constructing a linear decision function. For the linear function, it constructs an interval band on both sides of it, and if the training samples fall into the interval band, no loss is accounted for.…”
Section: Methodsmentioning
confidence: 99%
“…Amjadi et al [48] also observed lower hedonic odor scores and overall acceptance during storage of white cheese wrapped in biodegradable films containing zinc oxide nanoparticles. The fact that this study only examined appearance and odor variation during the storage period of packaged products emerged as a limitation, since the variations in terms of flavor and texture that food products may be subjected to during storage could not be identified [49][50][51][52][53]. Therefore, future research could envisage tests including all sensory modalities.…”
Section: Variablesmentioning
confidence: 99%